Phenomenal intentionality - Kriegel, Uriah (Oxford ; New York : Oxford University Press, 2013)
Phenomenal intentionality is supposed to be a kind of directedness of the mind onto the world that is grounded in the conscious feel of mental life. This book of essays explores a number of issues raised by the notion of phenomenal intentionality.
The phenomenal intentionality research program / Uriah Kriegel -- Access problem / Michelle Montague -- Indexical thought / David Pitt -- Phenomenal presence / Christopher Frey -- Consciousness and synthesis / Colin McGinn -- Constructing a world for the senses / Katalin Farkas -- Phenomenal objectivity and phenomenal intentionality: in defense of a Kantian account / Farid Masrour -- Phenomenal intentionality and the role of intentional objects / Frederick Kroon -- Unconscious belief and conscious thought / Tim Crane -- Intellectual gestalts / Elijah Chudnoff -- Does phenomenology ground mental content? / Adam Pautz -- Phenomenality and self-consciousness / Charles Siewert.
Title from PDF title page (viewed on Apr. 9, 2013).
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Intentionality (Philosophy); Phenomenology; Intentionnalité (Philosophie); Phénoménologie.; phenomenology; PHILOSOPHY -- Mind & Body; Intentionality (Philosophy); Phenomenology